Simulation and Fabrication of Open-Type Boiler of Fish Cracker Production Line - Mohd Zaidi, Sidek; Mohd Syahidan, Kamarudin; Mohamad Nafis, Jamaluddin (Penerbit Universiti Malaysia Pahang, 2015)
Boiling process is performed at the final stage in fish cracker processing and it is a longest process. It creates a bottleneck and limits the daily production of fish cracker. Traditionally, fire woods are used to heat the boiler. The invention of diesel-fired boiler has improved the process but there are still some issues at the station. Therefore, a new boiler is designed to improve the boiling process by using LPG burner which has 2.9 % higher calorific value than diesel. The boiler designed was simulated to study the heat convection inside the boiler by using SolidWorks Flow Simulation to analyze the temperature distribution inside the new boiler. Multiple layers bottom plate of the boiler consist of an aluminium plate sandwiched between two stainless steel plates is used to increase the rate of heat transfer from the flame into the water inside the boiler. The result from the simulation proves that the multiple layers bottom plate of the boiler has a higher rate of heat transfer than the single layer plate where the time taken for water to boil is 42.2% shorter than the single stainless steel layer bottom plate boiler.